Mentalhygiene in Organisationen - Förderung seelischer Gesundheit in Organisationen zwischen gesellschaftlicher, institutioneller und personaler Verantwortung - Wittrahm, Andreas (European Journal of Mental Health, 2010)
Mental Health in Social Organisations: An organisation is a social arrangement which pursues collective goals and controls its own performance in structure and processes. Such organisations do not function in a vacuum: they all try to realise their goals depending on external conditions on the one hand and the professional and personal resources of their members on the other hand. If these do not fit, organisations often ask too much of the women and men they employ – mental diseases and demoralisation might follow such a permanent strain. By example of welfare-organisations primarily in Central Europe where the social framework is chang- ing, the research identifies the mechanisms that menace employees’ mental health. It examines the values, goals and structures that do not lose sight of the mental health of employees and provide them active protection. First, this includes organisational ethics that ensure the organisation’s goals are transparent and the paths leading to the implementation of the goals are subject to open discussion whenever external factors change. Second, organisations sensitive to issues of mental hygiene are also characterised by structures that involve their members and their employees in the discussion that identifies the best way for their organisation to carry out its goals. Third, an organisation that is well-designed from a mental hygiene aspect employs a personal development strategy that harmonises individual skills with the expectations towards the various roles and positions. And fourth, the prevention of mental diseases in social work demands for all members the chance of guided self-reflection concerning their roles and purposes as well as their participation in their team and in the whole organisation.